IMPROVING MANAGEMENT ACCOUNTING IN RAILWAY TRANSPORT ENTERPRISES: THE CASE OF “UZBEKISTAN RAILWAYS” JSC (American Journal of Business Management, Economics and Banking, 2025)
This article explores the theoretical and practical aspects of improving management accounting at “Uzbekistan Railways” JSC The study analyzes current challenges in aligning national accounting practices with International Financial Reporting Standards (IFRS) and examines the potential of introducing modern management tools, including the Balanced Scorecard (BSC), digital transformation instruments, and international auditing practices. Findings indicate that effective integration of these approaches can enhance financial transparency, increase operational efficiency, and support sustainable development of railway transport enterprises in Uzbekistan.